CHLORIDE SENSOR FABRICATION BASED ON SPE Ag/AgCl THROUGH CYCLIC VOLTAMMETRIC TECHNIQUE: SCAN RATE EFFECT - Mas'ud Asadullah; Sagir Alva; Ali Rinaldi; Rita Sundari (SINERGI, 2021)
The Cyclic Voltammetric (CV) technique is one of the Ag/AgCl fabrication processes. In electrochemical processes using this CV technique, the microstructure of the surface of a substrate or electrode can affect the scan rate. Thus, this study aims to identify the scan rate effect of the Cl-ion sensor fabrication process using the CV technique on the performance of the Cl-ion sensor. First, the CV process was carried out in one cycle to grow the AgCl layer on the Ag surface. Then, this process was carried out at varied scan rates of 20, 40, 60, 80, and 100 mV/s. After completing the Ag/AgCl fabrication process, it was followed by the characterization process, selectivity coefficient test, lifetime test, and validation test to compare the test results of the Cl SPE Ag/AgCl ion sensor with Ag/AgCl commercial. The results showed that the optimum Cl-ion sensor response was obtained at the scan rate of 60 mV/s. Then, based on the validation test, the Cl-ion in the two samples did not show significant differences. Therefore, it indicates that the SPE Ag/AgCl ion sensor has the same performance as the Ag/AgCl commercial.